2017
DOI: 10.1159/000474934
|View full text |Cite
|
Sign up to set email alerts
|

Acute Intravenous Calcium Antagonist for Suspected Hemiplegic Migraine – A Case Story

Abstract: Stroke mimics, like attacks of hemiplegic migraine, are challenging in acute stroke evaluation. We present a 28-year-old woman with a suspected hemiplegic migraine attack with left-sided hemiparalysis. Brain CT with perfusion imaging 1 h 54 min after symptom onset revealed hypoperfusion in the right hemisphere. The patient was treated with intravenous recombinant tissue plasminogen activator (rtPA) with no effect. After a subsequent intravenous verapamil infusion, the patient gained full motor function within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Gray and white matter atrophy with ex vacuo dilatation of the lateral ventricle, as seen in this patient, has also been reported in another child with this mutation [4] . During a stroke-like event of the right hemisphere, there was decreased perfusion with normal MRA, similar to what has previously been described in hemiplegic migraine perfusion imaging [14] . The extensive longitudinal neuroimaging in our report shows in one child the evolution of structural changes representing this spectrum of CACNA1A -related injury.…”
Section: Discussionsupporting
confidence: 83%
“…Gray and white matter atrophy with ex vacuo dilatation of the lateral ventricle, as seen in this patient, has also been reported in another child with this mutation [4] . During a stroke-like event of the right hemisphere, there was decreased perfusion with normal MRA, similar to what has previously been described in hemiplegic migraine perfusion imaging [14] . The extensive longitudinal neuroimaging in our report shows in one child the evolution of structural changes representing this spectrum of CACNA1A -related injury.…”
Section: Discussionsupporting
confidence: 83%
“…An accurate ophthalmological evaluation, including best-corrected visual acuity, slit-lamp biomicroscopy, intraocular pressure measurement, and indirect ophthalmoscopy, by excluding optical media, retinal, or optic nerve diseases, can help in the differential diagnosis. It has recently been observed that perfusion CT imaging can help in the decision-making process leading to the differential diagnosis of symptoms mimicking a stroke and, therefore, can direct to appropriate treatment (Nieuwkamp et al, 2010 ; Hansen et al, 2011 ; Miller and Goldberg, 2012 ; Campbell et al, 2013 ; Shah et al, 2013 ; Angermaier et al, 2014 ; Rath et al, 2017 ; Ridolfi et al, 2018 ; Granato et al, 2020 ). Diagnostic accuracy can be further improved by refining the diagnostic criteria of transient ischemic attacks, which can help to separate them from mimics (Lebedeva et al, 2018 ; Dolmans et al, 2019 ).…”
Section: Migraine Comorbidity As Judged By Neuroimaging Techniquesmentioning
confidence: 99%
“…13 A limited number of case reports as well as a short series of patients with MA have reported, in some cases, an abnormal PCT pattern. [14][15][16][17][18][19][20][21] The aim of the current study was to determine the clinical characteristics of MA as well as the frequency and patterns of PCT alterations, in a series of patients with MA mimicking acute ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…The depolarization wave causes vasodilation and an increase in regional cerebral blood flow (CBF), which has been termed spreading hyperemia, followed by a prolonged period of hypoperfusion lasting 1–2 h, called spreading oligemia 13 . A limited number of case reports as well as a short series of patients with MA have reported, in some cases, an abnormal PCT pattern 14‐21 …”
Section: Introductionmentioning
confidence: 99%